Potensi Reduksi Formalin dalam Ikan Asin Teri Nasi menggunakan Serbuk Limbah Kulit Bawang Putih - Amelia Handayani Burhan (MEDIA ILMU KESEHATAN, 2022)
Background: Food safety in the community is relatively low. This is evidenced by the fact that many food products contain harmful substances, such as the discovery of formalin anchovy salted fish in the city of Yogyakarta. This condition can threaten the health of the people of Yogyakarta City because many traders use anchovies as the main raw material in their cooking, such as in the manufacture of Angkringan Cat Rice, the typical cuisine of the city of Yogyakarta. This potential hazard can be suppressed by reducing the level of formalin that may be contained in anchovy before consumption, one of which is by utilizing the saponin content in garlic peel waste. Objective: This study aims to study the effect of the mass of garlic peel waste powder on formalin in salted anchovy samples Methods: The type of this research was a completely randomized design (CRD) with ten mass variations of garlic peel waste powder, namely 0, 1, 2, 3, 4, 5, 6, 7, 8, and 10 grams of powder in 50 ml of distilled water. This design is used to soak 1 gram of anchovy with formalin for 30 minutes at room temperature. Sampling was done by accidental sampling method at five traditional markets in Yogyakarta City. Formalin identification was carried out using the ET Group brand formalin test kit. Samples that have been treated are then re-determined the levels of formalin. Determination of formalin content was carried out by the acidimetric method. The effect test was carried out statistically with a confidence level of 0.05. Results: The highest decrease in formalin levels in the F7 treatment (soaking 1 gram of anchovy salted fish in 6 grams of garlic peel powder in 50 ml of distilled water for 30 minutes) reached 89.12%. However, with the addition of more powder (F8-10), it was seen that there was a decrease in the reduction ability of formalin by saponins. The statistical test showed that the mass of garlic peel waste powder affected reducing the level of formalin in anchovy salted fish (sig < 0.05). Conclusion: Garlic peel waste powder has the potential to reduce formalin levels in anchovy salted fish